REVITALISASI KELOMPOK TANI SEBAGAI MEDIA PENYULUHAN PERTANIAN ERA GLOBALISASI - Hariadi, Sunarru Samsi (Jurnal Ilmu-Ilmu Pertanian, 2005)
Since government decentralized in 1999, extension workers became local government official. In many districts, local government was not ready, so that agricultural extension and their institutions could not play their roles normally. Farmers groups could not be guidanced by extension workers effictively. Another hand, globalization era would increase competition of agricultural product sale, and farmers were not ready to do it. For answering about agricultural development in globalization era, farmers groups as agricultural extension media have to be improved, agricultural extension have to emphasize product quality and business activities, so that farmers groups can be success as learning forum, medium for cooperative actions, unit of production, and business unit.